1999
DOI: 10.1097/00004647-199904000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Transfer Function Analysis of Cerebral Hemodynamics in Patients with Carotid Stenosis

Abstract: This study evaluates the validity of the transfer function analysis of spontaneous fluctuations of arterial blood pressure (ABP) and blood flow velocity of the middle cerebral artery (MCAFV) as a simple, convenient method to assess human cerebral autoregulation in patients with carotid stenosis. Eighty-three consecutive patients with various degrees of carotid stenosis and 37 healthy controls were enrolled. The carotid stenosis was graded based on the diagnostic criteria of duplex ultrasound. Instantaneous bil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
106
0
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(121 citation statements)
references
References 23 publications
14
106
0
1
Order By: Relevance
“…Our analysis has covered up to 330 mHz range since this was the cut-off frequency of the built-in RC-filter in the fNIRS device. These bands are found to be very similar to those in related studies (Hu et al, 1999;Kuo et al, 1998;Obrig et al, 2000a;Franceschini et al, 2000;Toronov et al, 2000).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our analysis has covered up to 330 mHz range since this was the cut-off frequency of the built-in RC-filter in the fNIRS device. These bands are found to be very similar to those in related studies (Hu et al, 1999;Kuo et al, 1998;Obrig et al, 2000a;Franceschini et al, 2000;Toronov et al, 2000).…”
Section: Discussionsupporting
confidence: 89%
“…Since the B-band can at most accommodate one such spectral line, we merge the two bands B and C, to cover the 30-330 mHz band range. Previous researchers (Kuo et al, 1998;Giller et al, 1999;Hu et al, 1999) have also excluded the A-band since it was mostly mirroring the fNIRS baseline activity. Another plausible argument for excluding the A-band is that it is inherently a nonstationary process, which obviates signalprocessing tools requiring stationarity.…”
Section: Search For Periodicitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Autoregulation has been previously estimated via transfer function analysis between CBF (measured with transcranial Doppler ultrasound) and MAP (measured with finger plethysmography) [6,26,29]. In order to apply this method a high coherence between CBF and MAP is required, and this is achieved, for example, by inducing MAP oscillations with paced breathing.…”
Section: Discussionmentioning
confidence: 99%
“…In the frequency domain, transfer function analysis has shown that cerebral autoregulation has characteristic manifestations in the coherence function, amplitude and phase frequency response curves [29,31,32,[37][38][39][40][41][42]. In the frequency range DC-0.1 Hz, an active autoregulation is reflected by a reduction in coherence, as well as in the amplitude frequency response, since CBF variability tends to become more independent of fluctuations in ABP.…”
Section: Autoregulatory Mechanismsmentioning
confidence: 99%